1998
DOI: 10.1021/la9812368
|View full text |Cite
|
Sign up to set email alerts
|

Micellization Dynamics and Impurity Solubilization of the Block-Copolymer L64 in an Aqueous Solution

Abstract: The dynamics of the micellization of Pluronic® L64 (EO13PO30EO13, PEO/PPO = 2/3) was studied by employing the iodine laser temperature-jump technique. These studies show a more complex behavior than previously described. Three relaxation processes were observed, depending on the temperature at which experiments were performed. The first two of these relaxation processes are related to the unimer incorporation into micelles and the redistribution of micelles after incorporation of the unimers. The third relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
163
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(184 citation statements)
references
References 21 publications
19
163
2
Order By: Relevance
“…Both experiments show that low-molar-mass impurities (oligomers of repeating units 3) were, in L-64 and L-62, while no such contaminants were found in L-44, L-43, or 10R5. Such impurities could have a great effect on the system phase behavior [42]; hence both L-64 and L-62 were purified as follows: the polymer was first dissolved in plenty of THF (Aldrich, 99.9% anhydrous), and then the solution was titrated with twice-distilled hexane (Sigma, 99 + %) until the polymer precipitated. The above procedure was repeated three times, and then the precipitate was centrifuged and the polymer dried in a vacuum oven at 50 • C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Both experiments show that low-molar-mass impurities (oligomers of repeating units 3) were, in L-64 and L-62, while no such contaminants were found in L-44, L-43, or 10R5. Such impurities could have a great effect on the system phase behavior [42]; hence both L-64 and L-62 were purified as follows: the polymer was first dissolved in plenty of THF (Aldrich, 99.9% anhydrous), and then the solution was titrated with twice-distilled hexane (Sigma, 99 + %) until the polymer precipitated. The above procedure was repeated three times, and then the precipitate was centrifuged and the polymer dried in a vacuum oven at 50 • C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The large discrepancy among the reported cac values can be attributed to a broad unimerto-micelle transition, technical problems, and heterogeneity of commercial polymers. In particular it has been shown that impurities strongly affect L64 micellization (30). As a result, it is difficult to ascertain the presence of block copolymer micelles under the present experimental conditions for L64.…”
Section: Solubilization As a Function Of The Polymer Chemical Structurementioning
confidence: 83%
“…For Pluronic Ò surfactants, at lower temperature polymer remains as unimolecularly dissolved but at higher temperature more hydrophobic component present becomes insoluble causing turbidity in solution. At higher temperatures when micelles form, the minor insoluble component gets solubilized leading to transparent solution well below the CPT [49]. The formation of micelles, intermicellar particles, compactness and further disintegration of clusters shows similar turbidity-temperature behavior [47,48].…”
Section: Turbidimetrymentioning
confidence: 94%